69 Triage Administration of Ondansetron for Gastroenteritis in children; a randomized controlled trial. (21st October 2022) - Weill, Olivia; Labrosse, Mélanie; Levy, Arielle; Desjardins, Marie-Pier; Trottier, Evelyne D; Gravel, Jocelyn
Abstract: Background: Acute gastroenteritis is an important reason for emergency department (ED) consultation in children. Ondansetron is reported to be effective in reducing vomiting in children with gastroenteritis, leading to less intravenous rehydration and hospital admission. Objectives: The aim of this study was to assess the effectiveness of triage nurse-initiated administration of ondansetron for children with suspected gastroenteritis in the paediatric ED to reduce the number of patients requiring observation following the first physician assessment. Design/Methods: This was a randomized controlled trial performed in a tertiary care paediatric ED. All children 6 months to 17 years old who presented to the ED with at least four episodes of non-billous, non-bloody vomiting in the previous 24 hours and the last vomiting occurring within the previous 2h were eligible. The intervention consisted of administration of a liquid formulation of an adapted to weight dose of ondansetron at triage compared to a color- and taste-matched placebo. The primary outcome was the number of patients requiring observation after the first physician's evaluation. Secondary outcomes were the number of episodes of vomiting after receiving the intervention, length of stay in the ED, comfort, and the proportion of children who returned for a medical visit within 48 hours. A sample size of 248 participants was initially identified to have a power of 90% to find a 20% difference in the proportion of children needing observation following physician evaluation. Results: Because of multiple external factors, including the COVID-19 pandemic, recruitment was stopped before the expected sample size was reached. A total of 91 patients were included and randomized to receive ondansetron (n= 44) or a placebo (n=47) just after triage. The baseline characteristics of the participants was similar between the two groups. A total of 40 (45%) participants were discharged immediately after the first evaluation by the treating physician. This was similar for both groups 44% vs. 45%; (95% CI for the difference -20 to 19%). There was no difference between the two groups for the total length of stay (median 232 vs. 227 minutes; p= 0.677) and for the length of stay after being seen by the physician (72 vs. 68 minutes; p=0.821). There was no statistical difference between the two groups in the number of vomiting episodes (difference of 15%; 95% CI -2, 31), and proportion of participants needing a rescue medication (difference: 19%; 95%CI:-0.6 to 36%) or an intravenous rehydration (difference: 8; 95%CI:-6, 22). Conclusion: This study failed to demonstrate any benefit in using ondansetron at triage for children with presumed gastroenteritis.